2018
DOI: 10.1534/genetics.117.300374
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Genomic Prediction: Combining Different Types of omics Data Can Improve Prediction of Hybrid Performance in Maize

Abstract: The ability to predict the agronomic performance of single-crosses with high precision is essential for selecting superior candidates for hybrid breeding. With recent technological advances, thousands of new parent lines, and, consequently, millions of new hybrid combinations are possible in each breeding cycle, yet only a few hundred can be produced and phenotyped in multi-environment yield trials. Well established prediction approaches such as best linear unbiased prediction (BLUP) using pedigree data and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
136
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(146 citation statements)
references
References 67 publications
8
136
2
Order By: Relevance
“…It is also difficult and too expensive to genotype all individuals to apply GS, despite important economies of scales. Alternative approaches based on endophenotypes such as transcriptomes or metabolomes have been proposed to predict phenotypes (Fu et al 2012;Riedelsheimer et al 2012;Feher et al 2014;Ward et al 2015;Fernandez et al 2016;Guo et al 2016;Xu et al 2016;Zenke-Philippi et al 2016;Westhues et al 2017;Seifert et al 2018;Schrag et al 2018), but their relatively low throughput and high costs are still likely to hamper their deployment at a large scale. To increase genetic progress in this context, we propose a new approach in which we use NIRS as high-throughput phenotypes to make predictions at low costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also difficult and too expensive to genotype all individuals to apply GS, despite important economies of scales. Alternative approaches based on endophenotypes such as transcriptomes or metabolomes have been proposed to predict phenotypes (Fu et al 2012;Riedelsheimer et al 2012;Feher et al 2014;Ward et al 2015;Fernandez et al 2016;Guo et al 2016;Xu et al 2016;Zenke-Philippi et al 2016;Westhues et al 2017;Seifert et al 2018;Schrag et al 2018), but their relatively low throughput and high costs are still likely to hamper their deployment at a large scale. To increase genetic progress in this context, we propose a new approach in which we use NIRS as high-throughput phenotypes to make predictions at low costs.…”
Section: Discussionmentioning
confidence: 99%
“…We could show for wheat that for fixed material, NIRS collected on seeds, so before sowing, was efficient to run PS, which offers very interesting perspectives for this species. The studies on endophenotypic variations in maize (Riedelsheimer et al 2012;Fu et al 2012;Guo et al 2016;Schrag et al 2018), rice ) and wheat (Ward et al 2015) also demonstrated that the characterization of germinated seeds or seedlings was efficient to estimate kinships resulting in accurate predictions. These results are promising, but this needs to be tested for other species and on other datasets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of models based on transcript levels can be better or worse compared to those based on genetic markers depending on the trait. For example, transcriptome data performed better for predicting grain yield in hybrid maize populations, but genetic marker data performed better for predicting grain dry matter content in the same population 15 . Similarly, in a maize diversity panel, GP models that combined transcript and marker data only outperformed models using markers alone for certain traits 16 .…”
Section: Introductionmentioning
confidence: 99%
“…As this special issue cannot be all‐encompassing, many other promising and important future research areas, for example for mitigating the agricultural footprint in the ecosystem, such as improved nutrient use efficiency (Distelfeld et al ; Hawkesford ; Avin‐Wittenberg et al ), root architecture (Salvi ), or root‐microbe interactions specifically for nitrogen‐fixing cereals (Rogers and Oldroyd ; Mus et al ), are not itemized. Similarly, the manipulation of recombination at free‐will in our cereal crops (Lambing and Heckmann ), or a better molecular understanding of heterosis (Schrag et al ; Seifert et al ) and the introduction of a cost‐effective and reliable hybrid seed production system in cereals (Muehleisen et al ; Whitford et al ; Tucker et al ) have not even been touched upon. Thus, many global and societal challenges, but also truly exciting research opportunities, still lie ahead of us.…”
Section: Discussionmentioning
confidence: 99%